Synthesis and characterization of 3,3”-dihydroxy-[1,1’:4’,1”-terphenyl]-4,4”- dicarboxylic acid derivatives as precursors for functionalized Co-MOF-74-III materials - Crause, Annelmie (University of the Free State, 2017)
English: A series of new 4,4”-di[methoxyethoxymethoxy]-[1,1’:4’,1”-terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl] derivatives were synthesised as possible linkers for MOF-74-III derivatives. The following products were synthesised via Suzuki-Miyuara cross-coupling and characterized by a combination of FTIR and 1H NMR spectroscopy as well as MS spectrometry: 4,4”-di[methoxyethoxymethoxy]-2’,5’-dimethyl-[1,1’:4’,1”-terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl], (90 %); 4,4”-di[methoxyethoxymethoxy]-2’,5’-dihydroxy-[1,1’:4’,1”- terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl], (90 %); 4,4”-di[methoxyethoxymethoxy]- 2’,5’-bis-benzyloxy-[1,1’:4’,1”-terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl], (60 %) and 4,4”-di[methoxyethoxymethoxy]- 3’-[3-ferrocenylpropamide]-[1,1’:4’,1”-terphenyl]- 3,3”-di[methoxyethoxymethoxycarbonyl], (70 %). Novel methods were developed for the syntheses of these linkers, with a different structural orientation than these found in literature. A generalized method, using methoxyethoxymethoxychloride (MEMCl), was developed for the protection of the hydroxy- and carbonyl-functionalities on these ligands Two MOF-74-III derivatives, Co-MOF-74-III-Me, and Co-MOF-74-III-NHCOCH2CH2Fc were successful synthesised from the methylated and ferrocene-containing linkers respectively. Co-MOF-74-III-Me is mesoporous with a pore width of 32.6 Å. Co-MOF-74-III-Me and Co-MOF-74-III-NHCOCH2CH2Fc are both thermally stable up to 180°C. All the 4,4”-di[methoxyethoxymethoxy]-[1,1’:4’,1”-terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl] derivatives showed irreversible redox couples for the carbonyl functionalities of the MEM-groups (-1500 mV vs. FcH/FcH+). An additional redox couple (-2160 mV vs. FcH/FcH+) was found for the amide functionality of the 4,4”-di[methoxyethoxymethoxy]- 3’-[3- ferrocenylpropamide]-[1,1’:4’,1”-terphenyl]-3,3”-di[methoxyethoxymethoxycarbonyl] ligand. Solid state cyclic voltammetry of Co-MOF-74-III-NHCOCH2CH2Fc, showed a redox couple (17 mV vs. FcH/FcH+) for the ferrocenyl fragments on the linkers, detected because electron transfer through the mesoporous material was fast enough.

Afrikaans: ‛n Reeks 4,4”-di[metoksie-etoksiemetoksie]-[1,1’:4’,1”-trifeniel]-3,3”-di[metoksieetoksiemetoksiekarboniel] derivate is as moontlike skakels vir MOF-74-III derivate gesintetiseer. Die volgende produkte is gesintetiseer via Suzuki-Miyuara kruiskoppeling en gekarakteriseer deur ‘n kombinasie van FTIR en 1H KMR spektroskopie, sowel as MS spektrometrie: 4,4”- di[metoksie-etoksiemetoksie]-2’, 5’-dimetiel-[1,1’:4’,1”-trifeniel]-3,3”-di[metoksieetoksiemetoksiekarboniel], (90 %); 4,4”-di[metoksie-etoksiemetoksie]-2’, 5’-dihidroksi- [1,1’:4’,1”-trifeniel]-3,3”-di[metoksie-etoksiemetoksiekarboniel], (90 %); 4,4”-di[metoksieetoksiemetoksie]- 2’, 5’-bis-bensieloksi-[1,1’:4’,1”-trifeniel]-3,3”-di[metoksieetoksiemetoksiekarboniel], (70 %);4,4”-di[metoksie-etoksiemetoksie]-3’-[3-ferroseniel-propaanamied]- [1,1’:4’,1”-trifeniel]-3,3”-di[metoksie-etoksiemetoksiekarboniel], (70 %). Nuwe metodes is ontwikkel vir die sintese van hierdie skakels, met ‘n ander strukturele oriëntasie as dié uit die literatuur. ‘n Algemene metode wat gebruik maak van metoksi-etoksimetoksichloried (MEMCl) is ontwikkel vir die beskerming van die hidroksi- en karboniel-funksionaliteite, op hierdie ligande. Twee MOF-74-III derivate, Co-MOF-74-III-Me en Co-MOF-74-III-NHCOCH2CH2Fc is suksesvol gesintetiseer vanaf die gemetileerde en ferroseen-bevattende ligande onderskeidelik. Co-MOF-74-III-Me is mesoporeus met ‘n poriegrootte van 32.6 Å. Co-MOF-74-III-Me en Co- MOF-74-III-NHCOCH2CH2Fc, is buide termiese stabiel tot en met 180°C. Al die 4,4”- di[metoksi-etoksimetoksi]-[1,1’:4’,1”-trifeniel]-3,3”-di[metoksie-etoksiemetoksie-karboniel] derivate het onomkeerbare redokskoppels getoon vir die karboniel-funksionaliteite van die MEM-groepe (-1500 mV vs. FcH/FcH+). ‛n Bykomende redokskoppel (-2160 mV vs. FcH/FcH+) was sigbaar vir die amiedfunksionaliteit van die 4,4”-di[metoksie-etoksiemetoksie]-3’-[3-ferrosenielpropaanamied]-[1,1’:4’,1”-trifeniel]-3,3”- di[metoksie-etoksiemetoksiekarboniel] ligand. Vastetoestand sikliese voltammetrie van Co-MOF-74-III-NHCOCH2CH2Fc, het ‘n redokskoppel (17 mV vs. FcH/FcH+) getoon vir die ferrosenielfragmente op die skakels, waargeneem omdat elektronoordrag vinnig genoeg deur die mesoporeuse materiaal kon plaasvind.
Keywords: Linkers; MOF-74-III; Suzuki-Miyuara cross-coupling; MEMCl; Ferrocene; Amide; Protecting groups; Redox couples; Surface area; Pore size; Dissertation (M.Sc. (Chemistry))--University of the Free State, 2017